Developing Journalism to Strengthen the Foundations of Democracy - Pramono, Dedi; Fadillah, Dani; Long, Bai (Komunikator, 2025)
This study aims to evaluate the development of scholarly discussions on the function of journalism within the field of communication studies. The keywords “communication” and “democracy” were used to search the Scopus database, resulting in 1,367 documents relevant to the scope of this research. Then, search criteria were applied by limiting the inclusion of articles to English-language journal publications published between 2013 and 2022. Based on these parameters, 527 documents met the research criteria. The data were subsequently processed using VOSviewer and Bibliometrix software. The outputs from both applications were combined to generate visual graphs that enabled the author to analyze and summarize the research findings. The study concludes that journalism, particularly in areas related to democracy, such as investigative journalism, press freedom, participatory journalism, and political dialogue, plays a significant role in advancing democratic processes. Future research on journalism and democracy may benefit from adopting thematic academic study formats and trending topics as reference points. The establishment of journalism grounded in democratic principles shows strong potential for success.